Study of plasma-assisted detonation initiation by quasi-direct current discharge. (January 2020) - Zhou, Siyin; Shi, Tianyi; Nie, Wansheng
To study the effects of quasi-direct current discharge plasma on the initiation of a pulse detonation engine at multiple locations, we proposed a double-zones quasi-direct current discharge plasma ignition scheme. Based on the establishment of the plasma-assisted detonation initiation model, the process of detonation wave formation in the mixture of hydrogen and air by single and double ignition zone were studied by numerical method. The wave structure, component evolution history, and Zeldovich–von Neumann–Döring curve after forming a stable detonation wave were all discussed. The simulation results indicate that due to its higher total ignition energy and the synchronous propagation of multiple compression waves, double-zone plasma ignition has a 17.9% shorter deflagration to detonation transition time and 14.2% lower detonation distance compared to the single-zone scheme. The double-zone scheme does not modify the peak flow field temperature and pressure when the stable detonation wave is formed, resulting in smoother pressure and temperature increases.